Functional health literacy and associated factors in older adults with type 2 diabetes mellitus - Tavares, Marina Silva; Medina, Luis Angel Cendejas; Lima, Glaubervania Alves; Pereira, Luis Fernando Costa; Rezende, Rute Tostas Machado; Amaral, Alexandra Castilhos Gomes; Teixeira, Carla Regina de Souza (O Mundo da Saúde, 2026)
The aim of the present study was to assess functional health literacy (FHL) among older adults with type 2 diabetes mellitus (T2DM) who performed self-monitoring of capillary blood glucose (SMCBG) and to analyze associated sociodemographic and clinical factors. This is an observational, analytical, cross-sectional study conducted with 106 older adults receiving care at health units in Ribeirão Preto, São Paulo, between February and October 2024. A sociodemographic and clinical questionnaire and the Brief Test of Functional Health Literacy in Adults (B-TOFHLA) were used. Descriptive analyses, Pearson’s chi-square or Fisher’s exact tests, and Spearman’s correlation were performed, adopting a significance level of 5%. The mean age was 69.97 years (SD=6.23), with a mean of 8.71 years of schooling (SD=4.49) and a mean monthly family income of R$ 2,833.41 (SD=1,911.38). Regarding FHL, 48.1% of participants had adequate levels, 8.5% borderline, and 43.4% inadequate. A statistically significant association was observed between education level and FHL categories (p<0.001). Positive correlations were also found between the B-TOFHLA score and years of schooling (ρ=0.492; p<0.001) and income (ρ=0.290; p=0.003), as well as a negative correlation with age (ρ=-0.206; p=0.034). Time since T2DM diagnosis was not significantly associated (ρ=0.081; p=0.411). It is concluded that more than half of the participants presented borderline or inadequate FHL, with education level being the main factor associated with performance on the B-TOFHLA. These findings highlight the need for continuous, clear, and tailored educational interventions adapted to the educational and socioeconomic conditions of older adults with T2DM.